PENGARUH KOMITE AUDIT DAN AUDIT EKSTERNAL TERHADAP MANAJEMEN LABA - Rezky Farras Khurnanto; Muchammad Syafruddin (Diponegoro Journal of Accounting, 2015)
The aim of this study is to examine the influence audit committe and audit external like PwC, Deloitte, KPMG and EY on earning management. Board size, firm size, leverage, and Performance used as control variable.The population in this study consists of all listed firm in Indonesia Stock Exchange in year 2013. Sampling method used is purposive sampling. The total number of samples in this study were 221 data, but after going through the stages of data processing, there are 15 of data outliers that should be excluded from the sample. Thus, the total number of eligible final sample was observed that 206 data. Variable earnings management, audit committee, external audit and the interaction between audit committee and external audit analyzed by Ordinary Least Square regression.            The empirical result of this study show that audit committee and audit external sifnificant influenced on earning management. There have negative influemced. But, the interaction between audit committee and external audit significantly positive effect on earnings management. This finding suggests that both the monitoring mechanisms functioning jointly within the firm would indicate potential increasing earnings management.